Analysis Of the Implementation of The Hybrid Contract Murabahah Bil Wakalah Agreement System in Griya Madani Financing Reviewed from Fatwa DSN No.04/DSN-MUI/IV/2000: Study at PT BPRS Metro Madani, Jatimulyo Branch Office - Syarif, Ahmad Hazas; Sya'adi, Nur; Fitriyani, Anggita (Journal of Contemporary Applied Islamic Philanthropy, 2023)
Purpose: PT BPRS Metro Madani Jatimulyo Branch Office offers a product called Griya Madani which is a combination of two types of contracts in one agreement, namely the murabahah bil wakalah contract (by order). Murabahah is a sale and purchase of the cost of goods plus a margin as profit from the seller. Along with its development, the murabahah contract was included in Islamic bank financing and combined with the wakalah contract so that it was known as murabahah bil wakalah. The provisions of murabahah bil wakalah are contained in Fatwa Number 04/DSN-MUI/IV/2000 point nine which among other things stipulates that when a bank wants to sell an item, the item must in principle become the property of the bank first. The purpose of this study was to analyze whether the hybrid contract murabahah bil wakalah contract system on Griya Madani financing at PT BPRS Metro Madani Jatimulyo Branch Office which was implemented at PT BPRS Metro Madani Jatimulyo Branch Office was by Fatwa Number 04/DSN-MUI/IV/2000 Methodology: The research method used a qualitative research method with a descriptive approach. Findings: The results of this thesis research conclude that the application of the hybrid contract murabahah bil wakalah contract system contained in the Griya Madani financing at PT BPRS Metro Madani Jatimulyo Branch Office is by Fatwa Number 04/DSN-MUI/IV/2000 concerning murabahah.